Extracellular buffering supplements to improve exercise capacity and performance: a comprehensive systematic review and meta-analysis - Farias de Oliveira, L.; Dolan, E.; Swinton, P. A.; Durkalec-Michalski, K.; Artioli, G. G.; McNaughton, L. R.; Saunders, B. (Sports Medicine, 2022)
Background: Extracellular buffering supplements [sodium bicarbonate (SB), sodium citrate (SC), sodium/calcium lactate (SL/CL)] are ergogenic supplements, although questions remain about factors which may modify their effect. Objective: To quantify the main effect of extracellular buffering agents on exercise outcomes, and to investigate the influence of potential moderators on this effect using a systematic review and meta-analytic approach. Methods: This study was designed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Three databases were searched for articles that were screened according to inclusion/exclusion criteria. Bayesian hierarchical meta-analysis and meta-regression models were used to investigate pooled effects of supplementation and moderating effects of a range of factors on exercise and biomarker responses. Results: 189 articles with 2019 participants were included, 158 involving SB supplementation, 30 with SC, and seven with CL/SL; four studies provided a combination of buffering supplements together. Supplementation led to a mean estimated increase in blood bicarbonate of + 5.2 mmol L-1 (95% credible interval (CrI) 4.7-5.7). The meta-analysis models identified a positive overall effect of supplementation on exercise capacity and performance compared to placebo [ES0.5 = 0.17 (95% CrI 0.12-0.21)] with potential moderating effects of exercise type and duration, training status and when the exercise test was performed following prior exercise. The greatest ergogenic effects were shown for exercise durations of 0.5-10 min [ES0.5 = 0.18 (0.13-0.24)] and > 10 min [ES0.5 = 0.22 (0.10-0.33)]. Evidence of greater effects on exercise were obtained when blood bicarbonate increases were medium (4-6 mmol L-1) and large (> 6 mmol L-1) compared with small (= 4 mmol L-1) [ß_Small:Medium = 0.16 (95% CrI 0.02-0.32), ß_Small:Large = 0.13 (95% CrI - 0.03 to 0.29)]. SB (192 outcomes) was more effective for performance compared to SC (39 outcomes) [ß_SC:SB = 0.10 (95% CrI - 0.02 to 0.22)]. Conclusions: Extracellular buffering supplements generate large increases in blood bicarbonate concentration leading to positive overall effects on exercise, with sodium bicarbonate being most effective. Evidence for several group-level moderating factors were identified. These data can guide an athlete`s decision as to whether supplementation with buffering agents might be beneficial for their specific aims.